2020
DOI: 10.1080/22221751.2020.1764396
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian pathogenicity and transmissibility of low pathogenic avian influenza H7N1 and H7N3 viruses isolated from North America in 2018

Abstract: Low pathogenic avian influenza (LPAI) H7 subtype viruses are infrequently, but persistently, associated with outbreaks in poultry in North America. These LPAI outbreaks provide opportunities for the virus to develop enhanced virulence and transmissibility in mammals and have previously resulted in both occasional acquisition of a highly pathogenic avian influenza (HPAI) phenotype in birds and sporadic cases of human infection. Two notable LPAI H7 subtype viruses caused outbreaks in 2018 in North America: LPAI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Indeed, mice are not naturally infected with influenza viruses and most strains require prior experimental adaptation to mice through successive passages from lung to lung [46]. However, several viruses of the H7 subtype have been shown to replicate efficiently in the mouse model without any prior adaptation [42][43][44]47]. Such a strain able to infect both birds and mammals is therefore ideal to study and better understand the host specificities related to PB1-F2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, mice are not naturally infected with influenza viruses and most strains require prior experimental adaptation to mice through successive passages from lung to lung [46]. However, several viruses of the H7 subtype have been shown to replicate efficiently in the mouse model without any prior adaptation [42][43][44]47]. Such a strain able to infect both birds and mammals is therefore ideal to study and better understand the host specificities related to PB1-F2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition human cases of infection with H7N9 viruses indicate that H7 viruses can, although rarely, infect humans [39,40]. Moreover, H7N1 subtypes isolated from ostrich and chicken were able to induce mortality and morbidity in mouse and ferret models without any prior adaptation, supporting a minimal level of zoonotic potential of H7N1 viruses [41][42][43][44]. To study further the effect of PB1-F2 in a potential species barrier crossing, we infected mice with various doses of our WT NLuc H7N1 strain.…”
Section: Replication Of H7n1 In Micementioning
confidence: 99%
“…H7 AIVs have resulted in both occasional acquisition of an HPAI phenotype in birds and sporadic cases of human infection. Laboratory studies have shown the ability of H7 LPAI strains to efficiently infect and propagate in mouse and ferret models, confirming the overall constant risk of AIV transmission to mammals and the need for constant monitoring of the virus in nature [114]. To summarize, contact between poultry farms and migrating waterfowl is a pronounced risk factor for AIV dissemination and reassortment.…”
Section: Interaction Of Wild Migratory Fowl With Other Influenza Reservoirs Such As Livestock Food Markets and Poultry Farmsmentioning
confidence: 84%
“…Previous studies have shown that H7 LPAIVs can replicate in the lungs of murine models [ 77 , 78 , 79 ]. The two H7 Korean AIVs were isolated from the lungs of infected mice without prior host adaptation.…”
Section: Discussionmentioning
confidence: 99%